**Re: can anyone teach this step by step by july 21 at 11 am p**
really lost said:

im still confused the exact question is really long and im trying to break it down but heres the whole question...........its tricky........but so is all math for me...... :x

perform the indicated operation and answer in lowest terms......

5a-5b-a^2+b^2/4a^2-4ab+b^2 x 4a^2-b^2/2a^2-1ab-b^2

Let's go term by term:

5a - 5b - a^2 + b^2

= 5(a - b) - (a^2 - b^2)

= 5(a - b) - (a - b)(a + b)

= (a-b)(5 - (a + b))

= (a - b)(5 - a - b) [1]

4a^2 - 4ab + b^2

= (2a - b)(2a - b) [2]

4a^2 - b^2

= (2a + b)(2a - b) [3]

2a^2 - 1ab - b^2

= (2a + b)(a - b) [4]

Now write 'em down:

[1] / [2] times [3] / [4]

You'll see you can cancel out (a - b), (2a - b) and (2a + b).

That leaves:

(5 - a - b) / (2a - b) : hope TK agrees

If you can't follow that, too bad so sad: I don't have a blackboard here!